Shell's influence on drying kinetics, color and volumetric shrinkage of Castanea sativa Mill. fruits - Delgado, T (2014)
Shell's influence on the drying behavior of two European chestnut (Castanea sativa mill.) varieties, Longal and Judia, was investigated in the present work. For this purpose, chestnuts of both varieties were dried in a hot air convection oven at 50.0 +/- 2.0 degrees C and air velocity of 1.0 +/- 0.1 m/s. The fruits were dried with and without outer shell, the axial dimensions, volumetric shrinkage and color being determined. Furthermore, the drying data was complemented for the first time with microscopic analyses of the shells. Longal and Judia drying behaviors were similar (moisture ratios less than 0.20 in 35 to 45 h), despite the microscopic differences in outer shell thickness (Judia: 556 +/- 43 mu m and Longal: 328 +/- 66 mu m) and cell format (smaller cells-Judia). After determining the suitability of several drying models, good results were obtained with the Page (Judia), and Two-term exponential and Modified Page models (Longal). Concerning fruit color, a slight decrease in fruit brightness and an increase on fruit yellowness were detected along drying for both varieties. Small volumetric shrinkage was observed (10-24%). From these results, both varieties seemed to be adequate to be used industrially to produce dried chestnut based products, showing similar drying behaviors. Regarding the influence of the outer shell on the drying process, it had a small impact on water removal. So, chestnuts can be dried with the outer shell, leading to a less expensive and non-time-consuming process because it is not necessary to peel the fruits before drying.